Combined Anastrozole and Antiplatelet Therapy Treatment Differentially Promotes Breast Cancer Cell Survival - Xulu, Kutlwano; Duarte, Raquel; Augustine, Tanya (Microscopy and microanalysis, 2020)
Thromboembolic disorders are the second leading cause of death in breast cancer. Antiplatelet therapy combined with cancer therapy is a potential treatment strategy against cancer-associated thromboembolic disorders; however, the efficacy of such dual treatment has not been established. This study reports novel findings on the response of hormone-dependent breast cancer cell lines (MCF7/T47D) following 24 h treatment with Anastrozole, combined with Aspirin and Clopidogrel cocktail; and Atopaxar. Neutral red and lactate dehydrogenase assays were conducted to assess viability and cytotoxicity respectively. Flow cytometric Annexin-V/PI assay was used to assess the mode of cell death. Morphological alterations were studied using scanning electron microscopy. Statistical analysis was conducted using Statistica V13. Definitive outcomes were established with flow cytometric detection of phosphatidylserine exposure and propidium iodide staining, complemented with ultrastructural analysis. Results showed that a few cells were undergoing death mainly through secondary necrosis. Morphological features suggesting induced cell motility (pseudopodia/ruffled membranes) were observed in both cell lines; notably, T47D cells presented pronounced features than MCF7 cells. Overall, these findings suggest that such combined treatment may differentially promote cell survival, inducing a more aggressive breast cancer phenotype.